2014
DOI: 10.1590/s1808-18512014130200322
|View full text |Cite
|
Sign up to set email alerts
|

Kyphosis in fractures: evaluation of digital measuring

Abstract: Objective: This study evaluates the manual and digital reliability and reproducibility of five methods of measuring deformity (kyphosis) in thoracolumbar burst fractures. Method: Ninety (90) tomographic images were evaluated and, in each case, kyphotic deformity was measured, both manually and digitally, through the five most relevant methods described in the literature. For the assessment of intraobserver error, 20 cases were measured again. Results: The results show that all five methods are highly reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These programmes allow superior options for image enlargements and adjustment for brightness and contrast that enable better vision and identification for key anatomical landmarks or other important parts of the spine. After drawing the lines through the vertebral endplates, the software measures the angle automatically, which further reduces the sources of error [9,10,21]. Thus, the current findings indicated that, after proper training, novice health professional raters had excellent reliability for digital Cobb measurement (ICC = 0.995–0.997) with a small range of SEM and MDC (Table 1).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…These programmes allow superior options for image enlargements and adjustment for brightness and contrast that enable better vision and identification for key anatomical landmarks or other important parts of the spine. After drawing the lines through the vertebral endplates, the software measures the angle automatically, which further reduces the sources of error [9,10,21]. Thus, the current findings indicated that, after proper training, novice health professional raters had excellent reliability for digital Cobb measurement (ICC = 0.995–0.997) with a small range of SEM and MDC (Table 1).…”
Section: Discussionmentioning
confidence: 68%
“…A conventional Cobb’s method showed a wide range of reliability data (ICC = 0.79–0.99) [68], which may suggest problems in data interpretation while using a plain film, including the difficulty of identifying a vertebral endplate, landmark of measurement, as well as defective angle measurement as a result of using different protractors, pencil, and ruler [10,21]. On the contrary, computer-based kyphosis measurement can be executed using several software such as AutoCAD and SurgimapSpine, depending on availability, accessibility, and familiarisation of the users [9,10]. These programmes allow superior options for image enlargements and adjustment for brightness and contrast that enable better vision and identification for key anatomical landmarks or other important parts of the spine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the five methods of kyphosis measurement used in our study, when performed digitally and compared to the manual technique, showed high reliability and reproducibility. 21 In our study, we used the computerized Surgimap® program, using the angular measurement tool in all cases and storing the measurements performed. More recently, studies have demonstrated the use of smartphone applications to measure various spinal parameters, including thoracolumbar kyphosis, with good accuracy and reliability.…”
Section: Discussionmentioning
confidence: 99%